Efficiency of different genera of arbuscular mycorrhiza fungi associated with cashew cultivars on maize growth and nutrient uptake - BALOGOUN, IBOURAIMAN; SAIDOU, ALIOU; KINDOHOUNDE, NARCISSE; AHOTON, ESSÈHOU LÉONARD; AMADJI, LUCIEN GUILLAUME; AHOHUENDO, BONAVENTURE COHOVI; BABATOUNDE, SÉVÉRIN; CHOUGOUROU, CHÈPO DANIEL; AHANCHEDE, ADAM (My University, 2015)
A pot experiment was carried out to assess the effect of different genera of arbuscular mycorrhiza fungi (AMF) associated with different cashew cultivars on maize growth parameters. The study was carried out at School of Crop Sciences, University of Abomey-Calavi in Benin during 45 days (from August 15 to September 30, 2013). The soil samples of 0-20 cm depth collected under different cashew cultivar trees were used for maize pot experiment. AMF density and diversity were previously studied on this soil. The four dominant genera of AMF isolated (Glomus; Glomus+Scutelospora; Glomus+Scutelospora+ Acaulospora and Glomus+Scutelospora+Acaulospora+Enthrophospora) from cashew cultivars were used solely or jointly as treatments. The experiment was laid out at a randomized completed bloc design with six replications. Plants’ root, above ground and root biomass, number of AMF spores, rate of root infection, and N and P uptake were assessed. Soil dominated by Glomus had induced significantly (P<0.05) high and vigorous plants compared with the other AMF genera. Furthermore, in the soil drenched with Glomus and Glomus+Scutelospora spores, we noticed the highest aboveground biomass production (1.47 ± 0.13 to 1.81 ± 0.23 g DM/plant), root biomass (7.35 ± 0.33 to 8.56 ± 0.65 g DM/plant) and rate of root colonization by the AMF spores (52.44 ± 4.20 to 59.00 ± 2.00%) compared with the other treatments. The results also showed that only Glomus+Scutelospora treatment induced the highest P and N uptake by maize plants (0.80 ± 0.03 and 1.55 ± 0.37 mg/plant respectively). Glomus and Glomus+Scutelospora association were effective in enhancing growth and development and nutrient uptake of maize. Soil from these cashew cultivars is an opportunity for production of inoculum to improve the growth and development of tree nursery.
Keywords: Anacardium occidentale; soil fertility; plant nutrition; growth and development; Benin